2020
DOI: 10.1371/journal.pone.0236538
|View full text |Cite
|
Sign up to set email alerts
|

Sites of vulnerability on ricin B chain revealed through epitope mapping of toxin-neutralizing monoclonal antibodies

Abstract: Ricin toxin’s B subunit (RTB) is a multifunctional galactose (Gal)-/N-acetylgalactosamine (GalNac)-specific lectin that promotes uptake and intracellular trafficking of ricin’s ribosome-inactivating subunit (RTA) into mammalian cells. Structurally, RTB consists of two globular domains (RTB-D1, RTB-D2), each divided into three homologous sub-domains (α, β, γ). The two carbohydrate recognition domains (CRDs) are situated on opposite sides of RTB (sub-domains 1α and 2γ) and function non-cooperatively. Previous st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…6,12,33 Furthermore, evidence suggests that SylH3's epitope is localized in or in proximity to subdomain 1β, not subdomains 1α or 2γ. 23 With that in mind, it is possible that SylH3 has allosteric effects on RTB similar to those reported by mAbs against the bacterial mannose-specific adhesin, FimH. 34 We therefore embarked on a study to define the molecular interactions between RT and SylH3 and JB4.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…6,12,33 Furthermore, evidence suggests that SylH3's epitope is localized in or in proximity to subdomain 1β, not subdomains 1α or 2γ. 23 With that in mind, it is possible that SylH3 has allosteric effects on RTB similar to those reported by mAbs against the bacterial mannose-specific adhesin, FimH. 34 We therefore embarked on a study to define the molecular interactions between RT and SylH3 and JB4.…”
mentioning
confidence: 87%
“…23 Rather, SylH3 and JB4 were assigned to epitope cluster 5, which is situated in or immediately adjacent to subdomain 1β. 23 To elucidate SylH3 and JB4's epitopes at high resolution, we determined the X-ray crystal structures of SylH3 and JB4 Fab fragments in complex with RT at 2.9 and 3.3 Å, respectively (Figure 1; Table S1). The structures revealed that SylH3 and JB4 Fabs interact primarily with subdomain 1β in a nearly identical fashion.…”
mentioning
confidence: 99%
See 3 more Smart Citations